Enhancing antibacterial activity through controlled ball milling: Structural, morphological and optical studies of ZnO nanoparticles - Benchelia, Souad; Messai, Youcef; Chetoui, Abdelmounaim; Mekki, Djamel Eddine (Nano-Structures & Nano-Objects, 2024)
Ball milling was used in order to produce ZnONPs with different mean crystallite sizes and shapes. XRD, FTIR, SEM, and PL characterizations were used to determine milling time's effect on ZnONPS's structural, morphological, and optical properties. XRD-analysis showed a decrease in particle size (43 to 12 nm) and a change in the lattice parameter c, from 5.177 to 5.198 Å. SEM analysis showed the formation of aggregated particles, evenly distributed. PL results indicated the appearance of new bands, which are associated to the formation of defects. Moreover, it was showed that milled ZnONPs enhanced antibacterial activity by decreased minimum inhibitory concentration (MIC) values. Indeed, MIC of Serratia marcescens and Shigella were initially, i.e., at t=0 h, 1024 µg/mL but, after of milling, it decreases to 32 µg/mL and 64 µg/mL, respectively. On the other hand, the MICs of Staphylococcus-coagulase-negative and Staphylococcus-aureus-ATCC23 decreased from 128 µg/mL and 64 µg/mL to 4 µg/mL and 2 µg/mL, respectively, as a function of milling time. In general, ball milling shows significant promise for enhancing antibacterial activity. However, this requires the control and optimization of the physicochemical parameters involved in the different stages of this process, as well as the understanding of the mechanisms underlying it. This is the subject of future research, with the obligation to broaden the scope of these investigations to other nanomaterials obtained in multiple ways.